2002
DOI: 10.1001/jama.288.22.2868
|View full text |Cite|
|
Sign up to set email alerts
|

Interventions to Enhance Patient Adherence to Medication Prescriptions

Abstract: Current methods of improving medication adherence for chronic health problems are mostly complex, labor-intensive, and not predictably effective. The full benefits of medications cannot be realized at currently achievable levels of adherence; therefore, more studies of innovative approaches to assist patients to follow prescriptions for medications are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
716
2
57

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,031 publications
(797 citation statements)
references
References 56 publications
22
716
2
57
Order By: Relevance
“…However, it is also possible that renal insufficiency may have led to undertreatment of patients with psychosis, as noted previously for patients with depression (15), and as has been demonstrated with cardiovascular disease (16).…”
Section: Discussionmentioning
confidence: 86%
“…However, it is also possible that renal insufficiency may have led to undertreatment of patients with psychosis, as noted previously for patients with depression (15), and as has been demonstrated with cardiovascular disease (16).…”
Section: Discussionmentioning
confidence: 86%
“…Adherence to medication is not necessarily related to sociodemographic factors such as age, sex, level of education or race [5] but rather that patients are less likely to adhere to those therapies that have adverse side-effects [6] are complex and/or last longer [5]. Evidence regarding all these issues has been mixed.…”
Section: Factors Related To Non-adherencementioning
confidence: 99%
“…Many reviews and clinical articles have included suggestions to reduce the complexity of the regimen, usually by decreasing the number of doses per day McDonald et al 2002), while others have concluded that there is no systematic difference between the effects of changing doses and other behavioral interventions (Peterson et al 2003). There are two published reviews on the impact of dosing schedules on adherence in chronic illness (Claxton et al 2001;Richter et al 2003).…”
Section: Introductionmentioning
confidence: 99%